Fanatical prospecting - Blount, Jeb (Ascent Audio, 2023)
Fanatical Prospecting gives salespeople, sales leaders, entrepreneurs, and executives a practical, eye-opening guide that clearly explains the why and how behind the most important activity in sales and business development-prospecting. Step by step, Jeb Blount outlines his innovative approach to prospecting that works for real people, in the real world, with real prospects. Learn how to keep the pipeline full of qualified opportunities and avoid debilitating sales slumps by leveraging a balanced prospecting methodology across multiple prospecting channels. This book reveals the secrets, techniques, and tips of top earners. You'll learn: why the 30-Day Rule is critical for keeping the pipeline full; why understanding the Law of Replacement is the key to avoiding sales slumps; how to leverage the Law of Familiarity to reduce prospecting friction and avoid rejection; the 5 C's of Social Selling and how to use them to get prospects to call you; how to use the simple 5 Step Telephone Framework to get more appointments fast; and much more! Fanatical Prospecting is filled with the high-powered strategies, techniques, and tools you need to fill your pipeline with high quality opportunities.